AN EXTENDED X-RAY ABSORPTION FINE STRUCTURE SPECTROSCOPY INVESTIGATION OF CADMIUM SORPTION ON CRYPTOMELANE (KMN8O16) - Randall S.R.; Sherman D.M.; Ragnarsdottir K.V. (My University, 1998)
The mobility of cadmium in the environment is strongly inhibited by sorption onto Fe and Mn (hydr)oxide minerals such as cryptomelane (KMn8O16). Adsorption experiments showed that cryptomelane was able to sorb two thirds of available cadmium from solution at pH as low as 2.0. Extended X-ray Absorption Fine Structure (EXAFS) spectroscopy was used to determine whether cadmium had sorbed to the external surfaces of the mineral, or migrated into the ~4.6 Å diameter tunnels which exist in the cryptomelane structure. The Mn coordination environment around sorbed cadmium (4.9±1.0 Mn at 3.65±0.02 Å) at pH 2.0 strongly indicates that the majority of sorbed cadmium is located inside the tunnels, and that it is displaced from the ideal tunnel cation position (special position 2a (0, 0, 0)). The oxygen coordination environment around cadmium (6.5±1.3 O at 2.24±0.02 Å) is consistent with this conclusion, but also suggests that sorbed cadmium is partially hydrated. The dominant tunnel cation (K+) was not significantly released to solution during cadmium sorption. Thus, it seems likely that cadmium exchanged with H+ in the tunnels rather than K+. This is supported by the lowering of pH during cadmium adsorption and corresponding charge balance calculations. Cadmium sorption at the tunnel sites is likely to be energetically favourable because it allows occupation of those tunnel sites which K+ cannot fill, thus resulting in a more effective balancing of the negative structural charge in cryptomelane. This is the first EXAFS study of cation sorption on a mineral with the hollandite structure.